In situ FTIR assessment of dried Lactobacillus bulgaricus: KBr disk formation affects physical properties. Issue 2 (2005) - Wolkers Wolkers, Willem F. Willem F.; Oldenhof Oldenhof, Harriëtte Harriëtte
Abstract : The overall protein secondary structure, heat‒induced protein denaturation, membrane phase behaviour, and glassy behaviour of Lactobacillus bulgaricus dried with sucrose were studied by Fourier transform infrared spectroscopy (FTIR) using two sample preparation methods. Samples for FTIR analysis were either prepared by mixing dried sample with KBr and compression into disks or by air‒drying of cell/sucrose suspensions on CaF2 windows. The results show that KBr compression causes protein unfolding and affects the thermo‒physical properties of dried cells when compared with cells that were dried on CaF2 windows and directly used for FTIR analysis without further manipulation. The protein denaturation temperature of samples prepared in KBr disks was decreased by more than 70 ° C compared to that of samples dried on CaF2 windows. In addition, hydrogen bonding interactions of the glassy cell/sucrose matrix were drastically affected by KBr compression. In contrast with samples dried on CaF2 windows, samples in KBr disks were not in a glassy state at room temperature. The membrane phase behaviour of the dried cells was also affected by preparation of the sample into KBr disks. We conclude that the KBr compression method for preparing samples for FTIR analysis affects conformation and physical properties of biomolecules in the dried state.